State Budget Proposal for Fiscal Year 2019 – Mozambique, Analysis of the Social and Economic Sectors - UNICEF (UNICEF Mozambique, 2019)
Key messages: 1. The envelope of resources for the 2019 State Budget is set to increase to MT 340 billion (from MT 303 billion in 2018), representing Mozambique’s largest nominal budget; however, once factoring in the depreciated currency and high inflation of recent years as well as high debt servicing payments, the purchasing power of this envelope –including for priority sectors– no longer represents a historical high. 2. The share of resources dedicated to investment in Mozambique has been steadily declining, particularly since 2015, due to frozen donor support and a crowding out effect by proportional increases in financial operations and recurrent spending. While in the 2019 Budget Proposal investment has increased to a 30 percent share of total spending, it is still far below the 40 percent norm registered a decade ago. 3. Over the past decade, the share of resources dedicated to the district level has increased at the expense of resources directed to the provincial level; meanwhile central-level expenditure has remained unchanged. In the 2019 Budget Proposal, the central level will, as usual, receive the most resources (64 percent), followed by districts (19 percent), provinces (15 percent), and then municipalities (2 percent). 4. Relative to the Government’s Five Year Plan (PQG), “Priority II: Develop Human and Social Capital” (i.e. priority economic and social sectors) is expected to receive the largest share of funding in the 2019 Budget Proposal. 5. The government has set the goal of allocating at least 60 percent of resources to the priority sectors (according to its methodology of excluding financial operations and debt servicing from the denominator); however, because financial operations and debt servicing have soared as a share of total spending, their 60 percent is no longer a reliable benchmark (e.g. priority sector allocations grew 3.5 times in nominal terms from 2009 to 2019 while the entire budget grew 4 times over the same period) . Proportional priority sector spending as a share of the entire budget (including financial operations and debt servicing) has dropped significantly in recent years. In the 2019 Budget Proposal, it is projected at 51 percent of the entire budget. 6. Among Priority Economic and Social Sectors, Water & Public Works, Transport & Communications, and Agriculture & Rural Development more than doubled their proposed allocations for 2019 relative to 2018 initial allocations. The Education, Health, and Social Action Sectors are also expected to receive a larger allocation than in 2018, but the increase will be smaller. The Infrastructure Sector (mainly the roads sub-sector) will be the only one experiencing a cut in allocation relative to the 2018 Budget.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento